2011
DOI: 10.1089/thy.2011.0064
|View full text |Cite
|
Sign up to set email alerts
|

Fluorodeoxyglucose Positron Emission Tomography in Primary Thyroid Lymphoma with Coexisting Lymphocytic Thyroiditis

Abstract: The frequent association of LT with primary thyroid lymphoma and the overlap of their clinical and pathologic findings pose a significant diagnostic challenge. While other imaging techniques are helpful in evaluating anatomic local and regional extent of primary thyroid lymphoma, 18F-FDG PET/CT can be of an added value in evaluating its metabolic activity and detecting regional and distant disease as well as in assessing response to treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 11 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…Strong evidence supports the use of FDG-PET for lymphoma in general because FDG-PET has superior diagnostic accuracy in lymphoma when compared with computed tomography and magnetic resonance imaging [51]. Although there are no specific studies assessing its usefulness in PTL, several case reports have documented its use in this rare disease [52,53]. PTL typically demonstrates avid uptake of fluorodeoxyglucose within the thyroid and any associated positive cervical lymphadenopathy [54].…”
Section: Imagingmentioning
confidence: 99%
“…Strong evidence supports the use of FDG-PET for lymphoma in general because FDG-PET has superior diagnostic accuracy in lymphoma when compared with computed tomography and magnetic resonance imaging [51]. Although there are no specific studies assessing its usefulness in PTL, several case reports have documented its use in this rare disease [52,53]. PTL typically demonstrates avid uptake of fluorodeoxyglucose within the thyroid and any associated positive cervical lymphadenopathy [54].…”
Section: Imagingmentioning
confidence: 99%
“…In our case series, tests for serum antithyroid antibodies were positive in all the patients and Hashimoto's thyroiditis (chronic lymphocytic thyroiditis) was in 20 patients, which indicates that there is a strong relationship between Hashimoto's thyroiditis and PTL. It has been reported that the patients with Hashimoto's thyroiditis have an overall 67~80-fold higher risk of developing thyroid lymphoma compared to the general population (Arabi et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Most of them represent isolated case reports and only one article concentrates on a small group of patients [Table 1]. [11121415161718] 18 F-FDG PET/CT has shown limited sensitivity in the assessment of low grade lymphomas such as those arising from MALT. In a report by Mikosch et al , the authors showed that intense 18 F-FDG uptake noted in the thyroid gland in their case with MALT lymphoma of thyroid was due to coexisting lymphocytic thyroiditis rather than the lymphomatous part and concluded that, 18 F-FDG PET imaging does not seem to be indicated in a patient with MALT lymphoma and known Hashimoto's thyroiditis.…”
Section: Discussionmentioning
confidence: 99%